Study of the role of soluble carbohydrates on floral bud abscission of pistachio trees - Talaie A.; Seyyedi M.; Panahi B. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
An experiment on pistachio cv. 'Ohadi' was conducted at Kerman Pistachio Research Center. Its objective was to determine the role of soluble carbohydrate concentration on flower bud abscission. The results showed that interaction of time and alternate bearing trees on soluble carbohydrate concentration of inflorescence buds was significant, but effect of alternate bearing on soluble carbohydrate concentration was not significant. The effects of interaction of time and alternate bearing trees on soluble carbohydrate concentration of leaves of pistachio trees were not significant. Soluble carbohydrates of on-year trees declined from June to July and caused flower bud abscission. But it increased during this time in off-year trees.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)